Replacing wild grazers with domestic livestock: effect on dung beetle diversity, biomass, size and ecosystem function in a semi-arid Namibian savannah - Nependa, Uemuvanga Jatandavara Heather (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.